2010
DOI: 10.1063/1.3448497
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic framework of dielectrophoretic deposition devices

Abstract: Numerical modeling and experiments are performed investigating the properties of a dielectrophoresis-based deposition device, in order to establish the electrokinetic framework required to understand the effects of applied inhomogeneous electric fields while moving particles to desired locations. By capacitively coupling electrodes to a conductive substrate, the controlled large-scale parallel dielectrophoretic assembly of nanostructures in individually accessible devices at a high integration density is accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 22 publications
3
62
0
Order By: Relevance
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
“…It was reported that a pair of counter-rotating fluid circulations could form near the microelectrodes [39]. This so-called electrothermal flow is a consequence of the interactions between the applied AC electric field and the Joule heating-induced gradients of fluid conductivity and permittivity [40,41]. Its magnitude is proportional to the fourth power of the local electric field.…”
Section: Introductionmentioning
confidence: 99%
“…The total-assembly yield rate (P) is the ratio of the number of electrode pairs assembled by SWCNTs to 360, and the single-assembly yield rate (Ps) is the ratio of the number of electrode pairs bridged by only one bundle of SWCNTs to 360 and the multi-assembly yield rate (Pm) is that of electrode pairs bridged by more than one bundles of SWCNTs. Both Figure 3(a) and 3(c) show that the P increased with both of voltage magnitude and DEP assembly time because more SWCNTs can be transported to the gap and assembled then, which is in agreement with other experiments and theoretical work [4][5][6][7][8][9]. As we know, in the range of 1 to 10 MHz, the total number of SWCNTs assembled depends very little on the frequency [6].…”
Section: Resultssupporting
confidence: 88%
“…There are mainly three forces acting on the SWCNTs during this procedure, such as DEP force, hydrodynamic forces of electro-thermal flow and AC electro-osmosis flow, and adhesive forces as shown in Figure 1. The first two are long-range forces, which determine the moving direction and speed of the SWCNTs in the suspension [4][5][6][7][8]. The z-direction of the forces push the SWCNTs toward the tip of the electrodes, and the x-and y-direction make the SWCNT align with the gap direction.…”
Section: Theory and Considerationmentioning
confidence: 99%
See 1 more Smart Citation